2019
DOI: 10.1152/ajpcell.00319.2018
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA HOXA11-AS induces type I collagen synthesis to stimulate keloid formation via sponging miR-124-3p and activation of Smad5 signaling

Abstract: Keloid, characterized by exuberant collagen deposition and invasive growth beyond original wound margins, results from abnormal wound healing. A recent microarray analysis identified homeobox (HOX) A11 antisense (HOXA11-AS) as a keloid-specific long non-coding RNA, although its potential role in keloid formation remains elusive. In this study, hematoxylin-eosin, Masson, and immunohistochemical staining of type I collagen (ColI) revealed abnormal arrangement and hyperplasia of fibers in keloid tissues along wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 30 publications
1
32
0
Order By: Relevance
“…In our analysis, many genes such as SMAD5, CAV1, JAG1, ROCK1 and STAT3 were positively predicted as downstream targets of miR-124, which was regarded as a potential miRNA binding site of hsa_circ_0029633. Previous studies have demonstrated that miR-124 plays a key role in multiple diseases including IPF by targeting SMAD5, CAV1, JAG1, ROCK1 or STAT3 [37][38][39][40][41][42], which is consistent with our findings. Previous studies have also shown that FOXC1 and HSPA1A are direct target genes of miR-223 [43,44], and these genes contribute to the pathogenesis of IPF via activating various signaling pathways.…”
Section: Discussionsupporting
confidence: 93%
“…In our analysis, many genes such as SMAD5, CAV1, JAG1, ROCK1 and STAT3 were positively predicted as downstream targets of miR-124, which was regarded as a potential miRNA binding site of hsa_circ_0029633. Previous studies have demonstrated that miR-124 plays a key role in multiple diseases including IPF by targeting SMAD5, CAV1, JAG1, ROCK1 or STAT3 [37][38][39][40][41][42], which is consistent with our findings. Previous studies have also shown that FOXC1 and HSPA1A are direct target genes of miR-223 [43,44], and these genes contribute to the pathogenesis of IPF via activating various signaling pathways.…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, previous studies have reported that non-coding RNAs, including miR-152-3p, miR-21 and miR-203 are differently expressed in keloid samples, which may contribute to the formation of keloids ( 18-20 ). Furthermore, lncRNA HOXA11-AS has been demonstrated to regulate the progression of keloids via miR-124-3p/Smad5 signaling ( 21 ). A recent study reported the involvement of the circRNAs and miRNAs regulatory networks during keloid scarring ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…Liang et al (26) also reported that miR-124 may regulate the EMT process by targeting snail family transcriptional repressor 2 to promote breast cancer metastasis, while Cui et al (27) suggested that miR-124 may induce hepatocellular carcinoma metastasis by targeting Slug. Additionally, homeoboxA11 has been shown to induce the formation of type I collagen in scars via the activation of miR-124-3p and the SMAD signaling pathway in the cavernous body (28). Thus, miR-124 contributes to the formation of fibrotic tissue in a variety of diseases by responding to the TGF-β and EMT signaling pathways.…”
Section: Discussionmentioning
confidence: 99%